On the stellar populations of galaxies at z = 9-11: the growth of metals and stellar mass at early times - Tacchella, Sandro; Finkelstein, Steven L.; Bagley, Micaela; Dickinson, Mark; Ferguson, Henry C.; Giavalisco, Mauro; Graziani, Luca; Grogin, Norman A.; Hathi, Nimish; Hutchison, Taylor A.; Jung, Intae; Koekemoer, Anton M.; et al. (The astrophysical journal, 2022)
We present a detailed stellar population analysis of 11 bright (H < 26.6) galaxies at z = 9-11 (three spectroscopically confirmed) to constrain the chemical enrichment and growth of stellar mass of early galaxies. We use the flexible Bayesian spectral energy distribution (SED) fitting code Prospector with a range of star formation histories (SFHs), a flexible dust attenuation law, and a self-consistent model of emission lines. This approach allows us to assess how different priors affect our results and how well we can break degeneracies between dust attenuation, stellar ages, metallicity, and emission lines using data that probe only the rest-frame ultraviolet (UV) to optical wavelengths. We measure a median observed UV spectral slope for relatively massive star-forming galaxies (), consistent with no change from z = 4 to z = 9-10 at these stellar masses, implying rapid enrichment. Our SED-fitting results are consistent with a star-forming main sequence with sublinear slope (0.7 ± 0.2) and specific star formation rates of 3-10 Gyr−1. However, the stellar ages and SFHs are less well constrained. Using different SFH priors, we cannot distinguish between median mass-weighted ages of ∼ 50-150 Myr, which corresponds to 50% formation redshifts of z 50 ∼ 10-12 at z ∼ 9 and is of the order of the dynamical timescales of these systems. Importantly, models with different SFH priors are able to fit the data equally well. We conclude that the current observational data cannot tightly constrain the mass-buildup timescales of these z = 9-11 galaxies, with our results consistent with SFHs implying both a shallow and steep increase in the cosmic SFR density with time at z > 10.